Characteristics of 1946 Cases of POEMS Syndrome in Chinese Subjects: A Literature-Based Study - Wang, Yong; Huang, Li-Bo; Shi, Yi-Hua; Fu, Huan; Xu, Zhen; Zheng, Guo-Qing; Wang, Yan (Frontiers in Immunology, 2019)
Abstract POEMS syndrome is a rare paraneoplastic disorder characterized secondary to a rare plasma cell dyscrasia. Here, we aimed to analyze the clinical characteristics of large sample cases of POEMS in Chinese subjects through making a review of the Chinese literature. Four databases were electronically searched from inception until October 2016. Case reports and case series were identified. Six hundred studies with 1946 participants were identified. The first case was reported in 1986, and the number of reported cases peaked in 2009 and 2010. The top seven provinces on the number of reported cases were in the south-east area of China. The top three departments on the number of published papers and reported cases were ordinally department of Neurology, Hematology and Endocrinology. The ratio of male to female was about 2.23. The range of age onset was from 10 to 81 years with the mean age of 46.39 (SD, 12.10 years). The initial symptoms of POEMS with peripheral neuropathy, edema and effusions, endocrinopathy, skin changes and organomegaly accounted for 60.44%, 15.72%, 9.87%, 8.05% and 2.13% respectively, and subsequently acquired above symptoms as the prevalence was 99.49%, 81.91%, 75.56%, 77.08% and 83.09% respectively. The present study would help to understand the clinical presentations of POEMS syndrome in the Chinese population